Analisis Pendapatan Usahatani Jagung Manis di Lahan Kering Subak Sembung, Kelurahan Peguyangan, Kota Denpasar - Putu Fajar Kartika Lestari; Ni Putu Anglila Amaral; Luh Putu Kirana; Bernabas Bulu (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
Subak Sembung is one of the sub-districts engaged in agriculture, especially in the sweet corn industry. Subak Sembung produces superior quality sweet corn. One of the superior productions in Subak Sembung, Peguyangan Village, is Sweet Corn Farming. The purpose of this study was to analyze the amount of income obtained from sweet corn farming and to find out the obstacles faced in Subak Sembung, Peguyangan Village, North Denpasar District, Denpasar City. This research was carried out from September to October 2022. The research location was determined by the purposive sampling method, while the research respondents were determined by census media. So that the sample in this study were 47 respondents. The data analysis method used in this research is the income analysis method, and the descriptive analysis method. Based on the results of research in Subak Sembung, Peguyangan Village, North Denpasar District, Denpasar City, the following conclusions can be obtained: The average sweet corn farming income earned by Subak Sembung, Peguyangan Village, is 16,072.116,68. The average income for sweet corn farming is 40,000,000.00. So that the average production cost for sweet corn farming is 23.927.883,32. And there are two obstacles, namely internal and external constraints.